Stunting In Children Aged 7 – 60 Months In The Work Of The Padang Laweh Public Health Center In 2022 - Purwati, Rati; Amalia, Neneng Suci; Sari, Evin Noviana (Sean Institute, 2022)
According to the World Health Organization, the prevalence of stunting becomes a public health problem if the prevalence is more than 20%. The number of nutritional status in Indonesia who experienced stunting in 2007 was around 36.8%, in 2013 it increased by about 37.2% and in 2018 it decreased by about 30.8%. Stunting is a condition of failure to thrive in children under five as a result of malnutrition so that children become too short for their age. Malnutrition can occur since the baby is in the womb and in the early days of the child's birth, but only appears after the child is 2 years old, where the nutritional state of the mother and child is an important factor in the child's growth (Rahayu A, 2018). The research method is descriptive analytic with a cross sectional approach (used is an analytical survey with a design objective). The statistical test used was the chi-square test. Through data analysis with statistical tests using the chi-square test with 68 children operating, the results of the study of children who were not exclusively breastfed were almost half of them, namely 28 children (41.2%) with stunting, while according to the data on children who were exclusively breastfed there were 9 children. (13.2%). From the test results, the p-value = 0.083 > 0.005 means that there is no significant relationship between exclusive breastfeeding and the incidence of stunting in children aged 7-60 months in the Padang Laweh Health Center Working Area in 2022